I must find the derivative using the product rule

Let me know so I can solve the problem for you thanks

yes, 2x squared multiplied by (3x-1) to the third

ok, y=2x^2 * (3x-1)^3

y'=4x[(3x-1)^3]+[3(3x-1)^2*3]*(2x^2)

y'=4x(3x-1)^3+18x^2(3x-1)^2=4x(3x-1)^3+18x^2(9x^2-6x+1)=162x^4-108x^3+18x^2+4x(27x^3-27x^2+9x-1)=162x^4-108x^3+18x^2+108x^4-108x^3+36x^2-4x=270x^4-216x^3+54x^2-4x

best me please if you like my answer thanks

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up